Deconvolution of continuous paleomagnetic data from pass‐through magnetometer: A new algorithm to restore geomagnetic and environmental information based on realistic optimization - Hirokuni Oda; Chuang Xuan (Geochemistry, Geophysics, Geosystems)
Abstract The development of pass‐through superconducting rock magnetometers (SRM) has greatly promoted collection of paleomagnetic data from continuous long‐core samples. The output of pass‐through measurement is smoothed and distorted due to convolution of magnetization with the magnetometer sensor response. Although several studies could restore high‐resolution paleomagnetic signal through deconvolution of pass‐through measurement, difficulties in accurately measuring the magnetometer sensor response have hindered the application of deconvolution. We acquired reliable sensor response of an SRM at the Oregon State University based on repeated measurements of a precisely fabricated magnetic point source. In addition, we present an improved deconvolution algorithm based on Akaike's Bayesian Information Criterion (ABIC) minimization, incorporating new parameters to account for errors in sample measurement position and length. The new algorithm was tested using synthetic data constructed by convolving “true” paleomagnetic signal containing an “excursion” with the sensor response. Realistic noise was added to the synthetic measurement using Monte Carlo method based on measurement noise distribution acquired from 200 repeated measurements of a u‐channel sample. Deconvolution of 1000 synthetic measurements with realistic noise closely resembles the “true” magnetization, and successfully restored fine‐scale magnetization variations including the “excursion.” Our analyses show that inaccuracy in sample measurement position and length significantly affects deconvolution estimation, and can be resolved using the new deconvolution algorithm. Optimized deconvolution of 20 repeated measurements of a u‐channel sample yielded highly consistent deconvolution results and estimates of error in sample measurement position and length, demonstrating the reliability of the new deconvolution algorithm for real pass‐through measurements.